2022
DOI: 10.1177/14799731221079305
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with participation in life situations in people with COPD

Abstract: Objective To examine potential determinants of participation frequency and limitations in people with Chronic Obstructive Pulmonary Disease (COPD). Methods For this secondary analysis, we grouped the following factors using the International Classification of Functioning, Disability and Health (ICF) components: age, psychological distress (Hospital Anxiety and Depression Scale (HADS)), gait aid use, supplemental oxygen use, grip strength, modified Medical Research Council Dyspnea scale, Short Physical Performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Body functions are the physiological functions of body systems and activities are the execution of a task or action by an individual [6]. Based on these classifications, each performance-based outcome measure was classified into functionality categories by consensus of the review team, considering analysed variables in the included studies and previous literature [22][23][24].…”
Section: Icf Classificationmentioning
confidence: 99%
“…Body functions are the physiological functions of body systems and activities are the execution of a task or action by an individual [6]. Based on these classifications, each performance-based outcome measure was classified into functionality categories by consensus of the review team, considering analysed variables in the included studies and previous literature [22][23][24].…”
Section: Icf Classificationmentioning
confidence: 99%
“…Failed weaning is a physical and psychological strain on patients as well as ICU nurses, which complicates the collaboration between nurses and patient. Previous research has demonstrated that psychological distress is significantly higher and common among patients with COPD [38]. Therefore, ICU nurses need to create encounters which promote positive experiences of care for patients with COPD.…”
Section: Comprehensive Understanding and Reflectionsmentioning
confidence: 99%
“…Patients with COPD often tell us how difficult it is to do the things they want to do because of their breathing problems but measuring “participation” objectively is often not undertaken. In the journal this month, D’Amore et al 2 report the factors determining participation based on the elements set out in the WHO’s definition of the construct. They found that reduced walking performance and psychological distress were the primary determinants of impaired participation.…”
Section: Daily Life For People With Copd It’s All About Taking Partmentioning
confidence: 99%